Muscle Mass Index Decline as a Predictor of Lung Function Reduction in the General Population - Joon Young Choi; Chin Kook Rhee; Sang Hyuk Kim; Yong Suk Jo (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background This study explores the link between muscle mass decline and lung function deterioration, which can worsen respiratory health by reducing exercise capacity and quality of life. The relationship between muscle mass index (MMI) changes and lung function in the general population remains unclear, especially as muscle mass fluctuates with aging. We aimed to clarify this dynamic relationship by examining how changes in muscle mass impact pulmonary function and the development of respiratory symptoms. Methods We utilized the Ansan and Ansung Cohort Study of the Korean Genome and Epidemiology Study (KoGES) database, a large‐scale prospective cohort, enrolling participants aged 40 to 69 years with lung function and body composition measurements. Over 12 years, data were collected biannually. The study assessed associations between changes in MMI and lung function trends, with cT1‐T3 calculated using the linear regression coefficient and stratified by tertile. Survival analysis was then performed to examine differences in time to first airflow obstruction (AFO) and exacerbation among the tertiles. Results A total of 2956 participants were enrolled in this study. At baseline, participants with higher MMI tended to be younger, had fewer co‐morbidities and exhibited better lung function. Those with a steeper MMI decline rate exhibited a more rapid forced expiratory volume in 1 s (FEV1) decline over a 12‐year follow‐up (cT1: 43.3 mL/year, cT2: 38.4 mL/year, cT3: 33.2 mL/year, p < 0.001). Forced vital capacity (FVC) decline were more pronounced in groups with greater MMI decline rates (cT1: 38.5 mL/year, cT2: 32.8 mL/year, cT3: 26.0 mL/year, p < 0.001). Although, the time to first AFO did not differ significantly among T1‐T3 groups, the time to first exacerbation related to wheezing event was significantly lower in cT3 group than in cT1 group (HR: 0.786, 95% CI: 0.629, 0.982). Conclusions A faster decline in MMI was associated with more rapid decline of both FEV1 and FVC and a higher risk of developing exacerbations of respiratory symptom. Although AFO was not associated with changes in MMI, further research is needed to explore the long‐term relationships between muscle mass and the effects of preventive interventions aimed at maintaining muscle mass and respiratory health.